PENGARUH KINERJA LAYANAN DAN KINERJA KEUANGAN TERHADAP KEMANDIRIAN DIMODERASI KETERSEDIAAN ANGGARAN BLU BBIB SINGOSARI - Dwi Nita Aryani; Aris Bachtiar (Jurnal Ilmu Manajemen, 2023)
This study examines and analyses the effect of service performance and financial performance on financial independence moderated by state budget (APBN) availability. This research was conducted at Singosari National AI Center, which has been assigned status as a Public Service Agency (BLU) since 2010. This type of causality research uses secondary data from 2011-2020. As the dependent variable, the BLU independent (Y) is measured by the independent ratio, efficiency ratio and effectivity ratio. The independent variables are service performance (X1) and financial performance (X2), and state budget (APBN) is the moderating variable. Service performance consists of the number of sales of frozen cement cows, training services, and livestock tourism. Meanwhile, the financial performance consists of the Current Ratio, Return on Assets, and Net Profit Margin. This study's statistical data analysis model uses Partial Least Square (PLS). The results showed that service performance positively and significantly contributed to financial performance. Service performance has a positive but insignificant contribution to BLU Independence. The service performance indicator that has the most decisive influence is frozen semen sales. Financial performance has a positive but not significant contribution to BLU Independence. The return on Assets is the financial performance indicator that gives an enormous positive contribution. Based on the test results of statistical data analysis, this study shows that the availability of APBN does not moderate the relationship between service performance and the financial performance of BLU Singosari National AI Center. These results contribute to the methodology to measure BLU performance and the factors that affect BLU's financial independence.